Restored Order Subordination and Freedom in 1 Peter - Carter, Steve (Studies in Biblical Literature, 2021)
The concept of subordination plays a prominent role in the paranesis of 1 Peter, and it appears too in the context of Christ's victory over the cosmic powers. It seems to presuppose some kind of given natural and social order in which people must live in their allotted place. But the author also sees his readers' subordination as conditioned by their status as free people, which he expounds in several passages. This investigation aims to clarify the meaning and relationship of the concepts of subordination and freedom in 1 Peter, with reference to the related idea of order. After an introduction that sets out the issues in detail, the first main section examines the three themes in the wider thought of the first century CE, and the second provides detailed exegesis of the key Petrine texts. A final chapter synthesizes this evidence and draws conclusions regarding the conceptuality of subordination and freedom expressed in the letter. The study presents the idea of "restored order" as a new interpretive key to the teaching and paranesis of 1 Peter and the significant New Testament tradition to which it belongs. It clarifies the important Petrine concepts of subordination and freedom, with that of order, within the letter as a whole and its constituent parts, and it illuminates the exegesis of various disputed texts and passages. Scholars and research students of 1 Peter and the wider New Testament will find here a compelling proposal to stimulate and inform their own engagement with the text.